Computer organization and design the hardware/software interface - Patterson, David A. (Elsevier/Morgan Kaufmann Publishers, 2009)
The classic textbook for computer systems analysis and design, 'Computer Organization and Design', has been thoroughly updated to provide a new focus on the revolutionary change taking place in industry today: the switch from uniprocessor to multicore microprocessors.
Keywords: Computer organization.; Computer engineering.; Computer interfaces.; elektronické knihy; electronic books